Selective packaging of mitochondrial proteins into extracellular vesicles prevents the release of mitochondrial DAMPs - Todkar, Kiran; Chikhi, Lilia; Desjardins, Véronique; El-Mortada, Firas; Pépin, Geneviève; Germain, Marc (Nature communications, 2021)
Most cells constitutively secrete mitochondrial DNA and proteins in extracellular vesicles (EVs). While EVs are small vesicles that transfer material between cells, Mitochondria-Derived Vesicles (MDVs) carry material specifically between mitochondria and other organelles. Mitochondrial content can enhance inflammation under pro-inflammatory conditions, though its role in the absence of inflammation remains elusive. Here, we demonstrate that cells actively prevent the packaging of pro-inflammatory, oxidized mitochondrial proteins that would act as damage-associated molecular patterns (DAMPs) into EVs. Importantly, we find that the distinction between material to be included into EVs and damaged mitochondrial content to be excluded is dependent on selective targeting to one of two distinct MDV pathways. We show that Optic Atrophy 1 (OPA1) and sorting nexin 9 (Snx9)-dependent MDVs are required to target mitochondrial proteins to EVs, while the Parkinson’s disease-related protein Parkin blocks this process by directing damaged mitochondrial content to lysosomes. Our results provide insight into the interplay between mitochondrial quality control mechanisms and mitochondria-driven immune responses. Mitochondrial content in extracellular vesicles (EVs) can enhance inflammation, although its role in noninflammatory conditions is unclear. Here, the authors show that mitochondria-derived vesicles target material to EVs, whereas Parkin directs damaged mitochondrial content to lysosomes, providing insight into mitochondria-driven immune responses.